Climate change risks on protected areas ecotourism: shocks and stressors perspectives in Ngorongoro Conservation Area, Tanzania. Issue 2 (3rd May 2016) - Mkiramweni, N. P.; DeLacy, T.; Jiang, M.; Chiwanga, F. E.
ABSTRACT: Protected areas are increasingly becoming important sites for ecotourism worldwide. Due to the high dependence on climate and natural ecosystems, protected areas ecotourism is, however, considered to be at risk of climate change. This study was conducted between January 2012 and April 2014 in the Ngorongoro Conservation Area with the aim of identifying climate related shocks and stressors and implied effects on ecotourism. Along with this aim, the study assessed ecotourism stakeholders' awareness and perceptions on climate change in the area. It was found through focus group discussion and semi-structured interview that recurrent droughts, political unrests in a neighbouring country, global terrorism and disease outbreaks have been the key shocks. It was found further that water shortages, vegetation change, biodiversity loss and recurrent livestock and human diseases are the key stressors. Understanding these provides grounds for conducting an in-depth vulnerability assessment and developing adaptation strategies for ecotourism.